Hyperspectral Indices and Image Classifications for Agriculture and Vegetation - Thenkabail, Prasad S; Lyon, John G; Huete, Alfredo (Taylor & Francis Group, 2018)
Evaluating the performance of various types of hyperspectral vegetation indices in characterizing agricultural crops, this volume discusses non-invasive quantification of foliar pigments, leaf nitrogen concentration of cereal crop, the estimation of nitrogen content in crops and pastures, forest leaf chlorophyll content, among other applications.